Tinjauan Sistematis Kebutuhan Asesmen Koneksi Matematis Berbasis Integrasi MCMA dengan PCM - Nurzanah Sri Hastuti; Iva Sarifah; Lussy Dwiutami Wahyuni (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
The mathematical connection assessment instruments that apply in high schools (SMA) generally still rely on dichotomous scoring, so that they are not able to describe students' partial understanding in detail. This study aims to examine the need for the development of a Multiple Choice Multiple Answer (MCMA) format instrument with a Partial Credit Model (PCM) through the Systematic Literature Review (SLR) approach. The study method refers to the Cochrane Handbook and the PRISMA protocol by analyzing 31 articles that meet the final inclusion criteria. The results of the study reveal that dichotomous scoring is limited in representing partial understanding PCM offers more accurate, fair, and informative measurements. The integration of MCMA with PCM has the potential to be developed as a mathematical connection assessment instrument based on a strong conceptual basis and can be used as a mathematical assessment innovation. Specifically, this study provides a starting point for further research related to the design, validation, and implementation of mathematical connection instruments at the high school level.Keyword: Mathematical Connections Assessment, Multiple Choice Multiple Answer (MCMA), Partial Credit Model (PCM)